(untitled) (AYUSHDHARA, 2024)
Ayurvedic deals with the physical, biological, social, and spiritual well-being of every individual. Ayurveda has its principles for justification based on Dosha, Dhatu, and Mala, called Tridosha (the three basic principles) having quality and function. The Tridosha principle forms the foundation of Ayurveda. It has been postulated that whatever physiological and pathological processes occur in the body, they are under the influence of three basic elements known as Vata, Pitta, and Kapha. Common Kapha dominant disorders in children are mainly breast milk-vitiated disorders. Aim and Objective- To collect and compile Kaphaja vyadhi in children and its treatment. Material and Methods- A literary study has been conducted through the various ancient texts of Ayurveda and contemporary textbooks. Various websites are also referred to in this context. Review method: literary research. Discussion and Conclusion: classical reference can be very well used to understand common Kaphaja vyadhi in children and its treatment.